Increasing the Brand Awareness of Sans Power’s Consumers in its Marketing Booklet - Claudia Marselina (Institute of Research and Community Outreach - Petra Christian University, 2019)
This paper aims at overcoming the problem faced by Sans Power by creating a marketing booklet as the solution. Sans Power is a trading company selling solar-energy products, like solar water pumps and solar panels. It offers a variety of solar water pumps based on the function, which are Submersible Solar Pump, Surface Solar Pump, and Solar Pool Pump. The main problem Sans Power is currently facing is the salespeople find it hard to explain to its customers and prospects about the uniqueness of buying Sans Power’s products. Therefore, a marketing booklet emphasizing the uniqueness of the products would be a solution. The marketing booklet will become the tool for the sales and marketing team to offer the unique benefits the customers can get. It will also make customers know more about Sans Power’s products and services, which can attract them increasing the sales. Keywords: promotion, promotional tool, marketing booklet, brand, brand awareness, unique selling point.